2012
DOI: 10.1007/s10840-011-9647-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of the Sprint Fidelis lead: survival analysis from a large single-center study

Abstract: This study presents a single-center experience on the natural history of the Fidelis lead. In our experience, lead survival declines at a lower rate when compared to prior reports. The risk of lead failure demonstrated a double peaked pattern at approximately 3 and 5 years. No identified variable was predictive of lead failure. LIA was effective in reducing the incidence and number of IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
10
1
1
Order By: Relevance
“…Our 3-year Fidelis survival rate of 93.5% is higher than what was seen in initial studies with shorter follow-up but is comparable to the 93% to 95.3% rates reported in 3 recent large studies with comparable follow-up time to ours. 9,10,12 In any case, our Fidelis survival rates are still lower than those that have been published by the manufacturer from the SLS and CareLink PLUS cohorts. 2 We found that female sex was the only significant clinical predictor of Fidelis lead failure and was associated with a doubling of the risk of lead failure.…”
Section: Prior Studies On Fidelis Lead Survivalcontrasting
confidence: 68%
“…Our 3-year Fidelis survival rate of 93.5% is higher than what was seen in initial studies with shorter follow-up but is comparable to the 93% to 95.3% rates reported in 3 recent large studies with comparable follow-up time to ours. 9,10,12 In any case, our Fidelis survival rates are still lower than those that have been published by the manufacturer from the SLS and CareLink PLUS cohorts. 2 We found that female sex was the only significant clinical predictor of Fidelis lead failure and was associated with a doubling of the risk of lead failure.…”
Section: Prior Studies On Fidelis Lead Survivalcontrasting
confidence: 68%
“…A relatively low lead failure rate was achieved with implantations which involved only double-coil lead in all patients. Tzogias et al [17] presented similar 9.7% failure rate in 971 patients with 6949 lead (double-coil) in a 5-year follow-up. Piot et al [15] found that singlecoil lead had over 3-times higher risk of fracture compared with double-coil lead.…”
Section: Lead Failurementioning
confidence: 80%
“…In the majority of papers published on SFL, only cumulative lead survival rate after 5 years is reported, the definition of failure is not consistent, and the lead type is mostly active. Reported lead survival ranges between 90% and 83%, mean/median follow‐up is less than 4 years, and the number of leads “at risk” at the time point 5 and 6 years is very low (e.g., less than 20% and 5%, respectively, in the paper by Cheung et al…”
Section: Discussionmentioning
confidence: 99%
“…Some of the current definitions of lead failure might overestimate true failure rate, as, for example, a continuous increase in low‐voltage impedance, a decrease in sensing values, and an increase in pacing thresholds were taken as “failure.” However, these changes might not be due to true lead failure, but due to normal lead degeneration or local tissue factors. We therefore decided to present both failure rates, a stricter as well as a more lenient one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation